Ant communities (Hymenoptera: Formicidae) in a primary tropical rainforest of Tawau Hills Park, Sabah and adjacent oil palm plantation area - Lai, Chin Hor (2008)
This study was carried out within the primary forest at Tawau Hills Park, Sabah, Malaysia and an adjacent oil palm plantation. The objectives of this study were to determine the effect of forest conversion to oil palm plantation area on ant diversity and to determine the effectiveness of all sampling methods used to sample ants at both study sites. Five sampling methods were used: arboreal baited pitfall trapping, extraction of ants from arboreal Asplenium nidus, Winkler bags, terrestrial baited pitfall trapping and hand collection using forceps through 100m belt transect. A total of 126 species of ants belonging to 47 genera and ten subfamilies were sampled in the primary forest of Tawau Hills Park meanwhile 82 species of ants belonging to 36 genera and seven subfamilies were sampled in the oil palm plantation. A total of 62 species of ants appeared exclusively in primary forest of Tawau Hills Park (i.e. not found in oil palm plantation). Assumption was made that some ant species were lost when primary forest was converted into oil palm plantation. In this research, ant species of Tapinoma melanocephalum and Anoplolepis gracilipes were recorded in oil palm plantation and Anoplolepis gracilipes was recorded in the primary forest of Tawau Hills Park. For terrestrial primary forest ants, manual transects gave the best results yielding 77 species whereas terrestrial pitfall method and Winkler's bags method yielded 42 and 44 species respectively. For arboreal ants in the primary forest, pitfall trap yielded 26 species meanwhile, extraction from Asplenium nidus root only recorded seven species. For terrestrial oil palm ants, manual transects gave the best results yielding 48 species whereas terrestrial pitfall method and Winkler's bags method yielded 21 and 24 species respectively. For arboreal ants in oil palm plantation, pitfall trap yielded 35 species meanwhile extraction from Asplenium nidus root only recorded 13 species. Based on the values of Shannon-Weiner diversity index and Evenness index, not all sampling methods in primary forest of Tawau Hills Park will record a higher value of these indexes compared with the indexes of oil palm plantation. This was mainly due to baited trapping method as this method recorded high abundance of Pheidologeton affinis and Lophomyrmex bedoti. Shannon-Weiner diversity index tend to be lower with these ant species of high abundance. In conclusion, this study showed that land conversion of primary forest into oil palm plantation decrease the total ant species number. Besides that, this land conversion also changes the species composition of the ant community, accompanied by an increase of invasive ant species in the oil palm plantation. Based on sampling efficiency that above 80% given by at least one species richness estimator for all the sampling methods used in this study, the conclusion that can be made is that all the sampling methods are effective to sample ants in both the primary forest of Tawau Hills Park and oil palm plantation.